Prognostic impact of left ventricular myocardial work in patients undergoing surgery for primary mitral regurgitation - Nabeta, Takeru; Peters, Ferande; Wu, Hoi W.; Chua, Aileen Paula; Palmen, Meindert; Tomšič, Anton; Marsan, Nina Ajmone; Bax, Jeroen J.; van der Bijl; Pieter (Springer Nature, 2025)
Purpose
Echocardiography-based, left ventricular myocardial work (LVMW) can assess LV function by incorporating LV afterload. This study aims to evaluate the prognostic value of LVMW indices in patients with primary mitral regurgitation (MR) undergoing mitral valve surgery.
Methods and results
A total of 306 patients (mean age 63 ± 12 years, 68% male) with severe, primary MR who underwent surgery, were included. All patients underwent transthoracic echocardiography and LVMW indices were assessed with commercially available ultrasound equipment before surgery. The mean LV global work index (LVGWI) was 1979 ± 537 mmHg% and 130 (42%) patients had impaired LVGWI (≤ 1900 mmHg%). During a median follow-up of 5.0 years (interquartile range, 2.5-8.9), 27 (8.8%) patients died after mitral valve surgery. Patients with impaired LVGWI or LV global longitudinal strain (LVGLS) (≤ 20%) had lower survival rates compared to the group with preserved (p < 0.01 and p = 0.02, respectively). While the likelihood ratio test suggests that LVGWI ≤ 1900 mmHg% provides additional prognostic information beyond the model including LVGLS (p < 0.05) for all-cause mortality, no significant improvement was observed in area under the curve, the C-index, or net-reclassification index.
Conclusions
In patients with severe, primary MR who underwent surgery, impaired pre-operative LVGWI was associated with a higher mortality risk, and may have incremental value beyond LVGLS, but requires further study for validation.